Optimalisasi Model Manajemen Strategik untuk Peningkatan Kualitas Pendidikan Islam - Muhammad Arifin; Zahruddin Zahruddin; Maftuhah Maftuhah (IAIN Sorong, 2021)
In general, the quality of Islamic educational institutions in Indonesia can be said to lag behind non-Islamic educational institutions. The quality of education is influenced by the quality of the education management it carries out. The better the quality of management of an educational institution, the quality of education produced will certainly be directly proportional. Changing times continue to occur and competition between educational institutions is also getting tougher. If you are not able to manage an educational institution properly, you will be left behind and it is possible to go bankrupt. One of these self-improvement efforts is the need to reformulate strategic management by considering the concept of a strategic management model. The purpose of this study is to explore a strategic management model for improving the quality of Islamic education. The research was carried out through an approach to library research methods. The results of this study have shown that in fact management strategy has a concept in Islam, so there are already Islamic educational institutions to run it according to Islamic guidelines in order to improve the quality of Islamic education.